PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU SATU PINTU KABUPATEN NIAS SELATAN - Wau, Fiktoriana Nismin Wiyarni (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this study is to know how much the influence of organizational culture and work environment against employee performance in the Investment Service and the integral licensing of one-namas district of Nias. This research uses an associative quantitative research and data analysis method used is a multiple linear regeneration analysis. The number of populations in this study were 23 employees. Sampling techniques in this study use saturated samples with the number of samples by 23 employees. This type of data of this research is the type of primary data that is the data obtained directly from the respondent. The data source of this research is employee. By using a questionnaire. Data collection using questionnaire or questionnaire. Data analysis technique using multiple linear regression analysis. The results of this study indicate that the organization's culture (X1) has a significant effect on employee performance (Y) where the organization's cultural variable (X1) is obtained value of Thengung (3,567)> ttable (1,725) and significant level of 0.133> 0.05. Furthermore, for the environmental variables (X2) have a significant effect on employee performance (Y) where Valcah Talital 3.962> Ttabel (1.725) and significant level of 0.064> 0.05 which means that partially the environmental variables (X2) influenced significantly inadequate performance (Y) performance variables. The result of the simultaneous test (F test), indicating that the value of FHITUN (3,494)> Ftabel (4.35) and significant level of 0.050> 0.05, it can be stated that the organization's cultural variable (X1) and the work environment (X2) simultaneously influence positive and significantly to the performance of employee performance (Y). For the determination coefficient (R2) of (25.9), so it can be interpreted that the motivation and the work environment are only able to explain the employee performance variable of 74.1% while the rest are not described in this study influenced by the work motivation variables and work disparin.